2021
DOI: 10.1142/s0218271821500905
|View full text |Cite
|
Sign up to set email alerts
|

Geometric phase for Dirac Hamiltonian under gravitational fields in the nonrelativistic regime

Abstract: We show the appearance of geometric phase in a Dirac particle traversing in nonrelativistic limit in a time-independent gravitational field. This turns out to be similar to the one originally described as a geometric phase in magnetic fields. We explore the geometric phase in the Kerr and Schwarzschild geometries, which have significant astrophysical implications. Nevertheless, the work can be extended to any spacetime background including that of time-dependent. In the Kerr background, i.e. around a rotating … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…and m is the mass of the fermion. In order not to change equation ( 8), the left handside of it can be multipled by γ 0 , γ 0 γ 0 = g 00 , then, it can be divided by g −1 00 i∂ 0 ψ = Hψ (10) where…”
Section: Fermions In Curved Spacetimementioning
confidence: 99%
See 1 more Smart Citation
“…and m is the mass of the fermion. In order not to change equation ( 8), the left handside of it can be multipled by γ 0 , γ 0 γ 0 = g 00 , then, it can be divided by g −1 00 i∂ 0 ψ = Hψ (10) where…”
Section: Fermions In Curved Spacetimementioning
confidence: 99%
“…There are no bound state solutions of the Dirac equation in Schwarzschild spacetime regardless of the value of the mass [7]. In some studies, approximative analytic solutions for the bound states are found [8], tunneling spectrum of vector particles and the Hawking temperature is investigated in [9], geometric phase in pseudo-Hermitian quantum mechanics is investigated [10], stationary solutions are discussed in [11]. QNMs can be described as the eigenmodes that show dissipative oscillations through spacetime and they can be produced by the perturbation theory [12].…”
Section: Introductionmentioning
confidence: 99%